From fossil-based to circular bioeconomy : a Swedish and Finnish pathway - Shurpali, Narasinha; Li, Yuan; Tampio, Elina; Lappalainen, Reijo; Mohammadi, Ali; Sandberg, Maria; Bhattarai, Hem Raj; Honkanen, Ella; Ebrahimian, Farinaz; Laaksonen, Ilmari; Blasco, Lucia; Jokinen, Noora; et al. (Springer Nature, 2025)
The transition from a fossil-based economy to a circular bioeconomy is a critical challenge and opportunity in the face of global climate change. Sweden and Finland, with their abundant forest resources and strong commitment to sustainability, are well positioned to lead this transition. The WoodPro project exemplifies this effort by exploring innovative ways to valorize forest residues into high-value products such as 2,3-butanediol (2,3-BDO), biopolymers and hydrochar. This perspective outlines the project’s multidisciplinary approach, which integrates advanced bioprocessing technologies with dynamic system analysis to optimize the sustainability and economic feasibility of these biorefining pathways. We highlight the potential of these interconnected processes to reduce greenhouse gas emissions, close nutrient loops and stimulate rural development, while positioning the Nordic countries as global leaders in the circular bioeconomy. The insights gained from this project highlight the importance of holistic, systems-based approaches in achieving carbon neutrality and offer a model for similar transitions worldwide.
Keywords: forest residues; biomass conversion; biochar; butanediol; polymers; GHG emission